Greening Household Behaviour Overview of Results from Econometric Analysis and Policy Implications - Serret, Ysé (OECD Environment Working Papers, 2014)
The second round of the OECD Survey on Environmental Policy for Individual Behaviour Change (EPIC) was implemented in 2011. A publication providing an overview of the survey data from over 12 000 households in eleven countries (Australia, Canada, Chile, France, Israel, Japan, Korea, the Netherlands, Spain, Sweden and Switzerland) is available.1 Follow-up econometric analyses were conducted in each of the thematic areas covered (energy, food, transport, waste and water), as well as on cross-domain comparisons in environmental attitudes and behaviours.2 This report presents a synthesis of main results from econometric analysis using the data from the 2011 EPIC survey, as well as policy implications